The mass transfer characteristics and energy improvement with various partially blocked flow channels in a PEM fuel cell. (1st September 2020) - Dong, Pengcheng; Xie, Gongnan; Ni, Meng
Abstract: In order to improve the mass transfer and the energy performance of a Proton Exchange Membrane Fuel Cell (PEMFC), five different kind of block shapes in the flow channel are proposed and evaluated numerically. It is found that the use of blocks in the gas channel enhances the mass transfer due to the generation of a nozzle-type effect in the channel. Results shows that the performances of PEMFCs with the five blocked channels [Cases B–F] can be improved comparing with that of the conventional flow channel without block [Case A], and Case D performs the best. The electrochemical conversion efficiency and effective power are improved by 15.58% and 15.77%, respectively. Further, by observing the block heights (0.4, 0.5 and 0.6) and spatial intervals (2.5, 5.0 and 8.0) of the above optimal shape [Case D] on the energy performances, these improvements can be raised to 17.09% and 16.95%, respectively. Highlights: Partially blocked flow channels are proposed for the energy conversion of a PEMFC. Effects of geometric parameters on mass transfer and energy performance are studied. The enhancement in mass transfer is attributed to the generation of a nozzle-type effect. The improvement in both energy efficiency and effective power is about 17%.